Kira-kira - Kadohata, Cynthia (New York : Atheneum Books for Young Readers, 2004)
Chronicles the close friendship between two Japanese-American sisters growing up in rural Georgia during the late 1950s and early 1960s, and the despair when one sister becomes terminally ill.
Newbery Medal/Honor.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), October 2009.
Booklist starred, January 2004.
Horn Book, October 2004.
Keywords: Death -- Fiction; Friendship -- Fiction; Japanese Americans -- Fiction; Sisters -- Fiction; Death -- Fiction; Friendship -- Fiction; Japanese Americans -- Fiction; Sisters -- Fiction; Georgia -- History -- 20th century -- Fiction; Georgia -- History -- Fiction